Food, love and resistance: lessons on reimagining social reproduction from East Bay housing cooperatives - Guner, Sibel (Department of Environmental and Geographical Science, 2024)
Western cities are painfully lonely. Their residents are working more, eating worse, and missing community. An ideology that values capital production over human wellbeing has resulted in extensive systems governing the production of economic goods while restorative social practices are squeezed to the margins. In urban housing, this manifests as atomized nuclear households that maximize private resources and a focus on waged work, often sustained invisibly by the labour of feminized bodies. Yet across the San Francisco Bay Area, informal housing cooperatives challenge this trend by building detailed systems of care that reframe residents' relationship with the realm of social reproduction by collectivizing domestic labour. Among the social reproduction practices being organized, the food system stands out for its embodied nature and ability to serve as at once social, cultural, and political – it is the heartbeat of these homes. Using the communal food system as an entrypoint for analysis allows us to interrogate how such housing projects address the challenges of urban capitalism while complicating assumptions across the field of urban studies that such spaces inherently improve the state of urban crisis today. This research explores the question: How do food systems in East Bay housing cooperatives model ways to build non-extractive systems of care in the context of contemporary urban crisis? This investigation is approached with embedded research in two Bay Area housing cooperatives to examine the motivations, counter-politics, and impacts of these spaces on their members. Findings reveal that many residents see the practise of collectivising their home as part of a greater vision for political change, at the same time that unconscious bias limits the accessibility of these homes and can risk reproducing gendered labour struggles. The systems in housing cooperatives are thus not an end goal but an ongoing negotiation that can lead to improved conditions only with attention, care, and critical awareness of the need for social and labour justice to extend into the domestic sphere.